Localized bullous pemphigoid on sites of radiotherapy and lymphedema in the same patient - Manikoth P Binitha; Veeravalli V Vishnu; Sukumarakurup Sreekanth; O K Reena Mariyath (Wolters Kluwer Medknow Publications, 2014)
Bullous pemphigoid (BP) is a blistering disorder due to autoantibodies to the epidermal basement membrane zone. The triggering factor could be localized damage to the skin by physical or chemical agents. We report a case of a 68-year-old woman with a three year history of oral lesions of BP following radiotherapy for carcinoma of the hypopharynx, and a three month history of BP over lymphedematous sites on the right hand and right lower limb. Localized BP induced by radiotherapy or lymphedema is rare; both factors working simultaneously in the same patient is even rarer.